Spatiotemporally Controlled Ablation of Klf5 Results in Dysregulated Epithelial Homeostasis in Adult Mouse Corneas - Loughner, Chelsea L. (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: Corneal epithelial (CE) homeostasis requires coordination between proliferation and differentiation. Here we examine the role of cell proliferation regulator Krüppel-like factor 5 (Klf5) in adult mouse CE homeostasis. METHODS: Klf5 was ablated in a spatiotemporally restricted manner by inducing Cre expression in 8-week-old ternary transgenic Klf5(LoxP/LoxP)/Krt12(rtTA/rtTA)/Tet-O-Cre (Klf5(Δ/ΔCE)) mouse CE by administering doxycycline via chow. Normal chow-fed ternary transgenic siblings served as controls. The control and Klf5(Δ/ΔCE) corneal (1) histology, (2) cell proliferation, and (3) Klf5-target gene expression were examined using (1) periodic acid Schiff reagent-stained sections, (2) Ki67 expression, and (3) quantitative PCR and immunostaining, respectively. The effect of KLF4, KLF5, and OCT1 on gastrokine-1 (GKN1) promoter activity was determined by transient transfection in human skin keratinocyte NCTC-2544 cells. RESULTS: Klf5 expression was decreased to 23% of the controls in Klf5(Δ/ΔCE) corneas, which displayed increased fluorescein uptake, downregulation of tight junction proteins Tjp1 and Gkn1, desmosomal Dsg1a, and basement membrane Lama3 and Lamb1, suggesting defective permeability barrier. In transient transfection assays, KLF5 and OCT1 synergistically stimulated GKN1 promoter activity. Klf5(Δ/ΔCE) CE displayed significantly fewer cell layers and Ki67(+) proliferative cells coupled with significantly decreased cyclin-D1, and elevated phospho(Ser-10) p27/Kip1 expression. Expression of Krt12, E-cadherin, and β-catenin remained unaltered in Klf5(Δ/ΔCE) corneas. CONCLUSIONS: Klf5 contributes to adult mouse CE homeostasis by promoting (1) permeability barrier function through upregulation of Tjp1, Gkn1, Dsg1a, Lama3, and Lamb1, and (2) basal cell proliferation through upregulation of cyclin-D1 and suppression of phospho(Ser-10) p27/Kip1, without significantly affecting the expression of epithelial markers Krt12, E-cadherin, and β-catenin.